SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PERSEDIAAN - Suryanto, Suryanto (Bina Nusantara University, 2008)
The research purpose is to analyze and design the Accounting Information Systems sales and inventory system that runs as well as identifying the needs and requirements of the new system that is made to fix the weaknesses in systems and sales. The research method used is the method of analysis and design methods. Methods of analysis by analyzing the problems in the current system, identify information needs and system requirements. The design method used is the database design, form and appearance of the screen. The results to be achieved is to produce a draft of Accounting Information Systems sales and inventory system that can find solutions to existing systems with computerized systems that can help the company deal with the problems in the system is running. Conclusions obtained are that the Information System Accounting Information and the sale of inventories, which were given suggestions and solutions for computerized systems can assist company management in the decision making process because it can generate reports more accurate and faster than less efficient systems. With the use of Accounting Information Systems sales and inventories, companies can overcome the problems encountered so far.Keywords: accounting information systems, sales, inventory